HARD BALANCING RUSIA DAN TURKI DALAM KONFLIK SURIAH 2012-2015 - Haydhar Muhammad Bachtiar; Agussalim Burhanuddin (Departemen Ilmu Hubungan Internasional Univesitas Hasanuddin, 2019)
The Syrian conflict that has been raging since 2011, has involved external actors including Russia and Turkey in a rivalry model of “hard balancing.” Those two countries support different contested parties in the Syrian conflict. This article is aimed to describe the background, forms, and the impact of the hard-balancing rivalry between Russian and Turkey in the conflict. Russia’s involvement in the conflict is to back up Bashar al Assad’s regime politically and militarily in order to protect its military and economic interests in the region, while Turki provides supports to the rebels. The rivalry between the the two countries has made the Syrian conclict more complicated and long-drawn. Konflik di Suriah yang berlangsung sejak tahun 2011 telah melibatkan aktor eksternal termasuk Rusia dan Turki dalam bentuk hard balancing dengan mendukung pihak berbeda dalam konflik Suriah. Tulisan ini bertujuan untuk mendeskripsikan latar belakang, bentuk, serta dampak rivalitas hard balancing Rusia dan Turki dalam konflik Suriah. Kehadiran Rusia dalam konflik ini untuk mendukung rezim Bashar al Assad secara politik dan militer dan melindungi kepentingan militer dan ekonominya di kawasan, sedangkan Turki memberikan dukungan terhadap kelompok pemberontak. Rivalitas kedua negara tersebut mengakibatkan konflik Suriah semakin kompleks dan berkepanjangan.